Information systems architecture and technology. proceedings of 38th International Conference on Information Systems Architecture and Technology – ISAT 2017 /: proceedings of 38th International Conference on Information Systems Architecture and Technology – ISAT 2017. Part III : (2018) - Unknown
No abstract available